PEMBELAJARAN KARAKTER ANAK USIA DINI BERBASIS ISLAM MODERAT - Gusnarib, Gusnarib; Dulumina, Gunawan B. (State Institute of Islamic Studies (IAIN) Palu, 2020)
The inculcation of character values ​​and wisdom in early childhood is a very urgent matter because, it is our shared responsibility that in children's daily lives will be reflected in the attitudes and behavior of children and how to deal with personal problems. Education as a process of intelligence through learning so that teachers and parents must be responsible for making a person not only know the values ​​of goodness alone, but can make the children realize the values ​​of virtue in daily life for the realization of tough characters and noble personality. Learning moderate Islamic character values ​​can be carried out properly and maximally when all parties. Cooperating and doing the same through a policy or regulation of school leaders, as a policy maker and the interests of an educational institution based on values. Basically learning activities, in addition to making students master competencies (material) that are targeted, are also designed to make students know, realize or care, and can internalize values ​​and make them behave in their lives.